(untitled) (Journal of Geography and Environmental Management, 2022)
The relevance of the study of landscape diversity has become one of the current directions of modern geographical research, allowing to obtain new scientific and practical results in the field of nature management and environmental protection. A comprehensive study and assessment of the diversity of the landscapes of the region is due to the increasing anthropogenic impact on its natural environment. The transformation of natural landscapes in the study area is associated with the raw materials orientation of its economy. As a consequence of the development, we have a wide variety of degrees and types of modifications of natural geosystems. The main results of the assessment of the landscape diversity of the territory of the Tobol river basin within the Kostanay region, performed using GIS, are presented. Landscape diversity evaluation performed using series of landscape diversity indices: uniqueness, relative wealth, landscape mosaic, landscape complexity, landscape fragmentation and the entropy measure of the complexity of landscape drawing (The Shannon index). The factors that determine the landscape diversity of the study region are considered. The results of cartographic analysis of the landscape diversity of the region are presented. A map of the landscape diversity of the territory of the Tobol River basin within the Kostanay region according to the Shannon diversity index has been compiled.